Comparative analysis of sokal’s equations versus load-pull implementation of class E low-pass network - Boodhoo Kirish; Farid Zubir; Mohamad Kamal A. Rahim; Shaharil Mohd Shah (Institute of Advanced Engineering and Science, 2020)
In this paper, class E power amplifiers (PA) aimed at frequency bandwidth of 3.4 GHz to 3.6 GHz (LTE 42) and 3.6 GHz to 3.8 GHz (LTE 43) respectively are designed with objective of attaining high efficiency. The viability of Sokal’s equations for present communication systems aimed at GHz are analyzed for high efficiency using HEMT (high-electron-mobility transistor) on Nitronex NPTB00004 as opposed to the Bipolar Junction Transistor used by Sokal in 1975. Load-pull configuration techniques aimed at the drain is implemented at the output matching network (OMN) and benchmarked against Sokal’s equation. At the OMN, to suppress harmonics, band-pass filters are employed for the LTE 42 and 43 respectively. Sokal’s equation shows that the drain must be conjugately matched before his equations are applied at the OMN. The efficiency at 3.4 GHz obtained for Sokal’s circuit is at 67 % and gain of 9.3 dB. More than 65% efficiency is obtained from load-pull network at 3.4 GHz to 3.76 GHz before filter implementation while showing gain above 7.8 dB. After filter addition at OMN, the efficiency is above 65% and gain above 8 dB for dual - band having bandwidth of 3.4389 GHz - 3.542GHz and 3.6569GHz - 3.8GHz.